Parasitemia of Male White Mice (Mus musculus L.) DDY Strain Infected with Trypanosoma evansi Pidie and Pemalang Isolate - Febiola Rama Sari; Yudha Fahrimal; Ummu Balqis; Didik T Subekti; Aprilia Wardana (Universitas Syiah Kuala, 2014)
This study aimed to find out the parasitemia of DDY white mice infected with T. evansi of Pidie and Pemalang isolates obtained from Bbalitvet Bogor. A total of 12 mice were divided into 3 treatment groups. Group 1 (K1) without any treatment, group 2 (K2) was inoculated with 104 T. evansi Pidie isolate, and group 3 (K3) was inoculated with 104 T. evansi Pemalang isolate. Parasitemia examination was carried out every two days and the level of parasitemia was observed as well. Parasitemia examination was conducted until all mice died. Parasitemia of mice infected with Pidie isolate was characterized by rapid rise of parasitemia in blood (107-108/mL of blood) in a short time (2-4 days) since first parasitemia was detected and followed by death at day 4. The parasitemia of mice infected with Pemalang isolate increased in the blood (108-109/mL of blood) on day 4 and maintained for a few more days and then fluctuated for a few more days before the animal was dead. In conclusion, there was the difference in parasitemia level between Pidie and Pemalang isolates. Key words: Trypanosoma evansi, parasitemia, Pidie isolate, Pemalang isolate